Locations and mucosal lesions responsible for major gastrointestinal bleeding in patients on warfarin or dabigatran - Kolb, Jennifer; Brückmann, Martina (Digestive diseases and sciences, 2018)
Different oral anticoagulants may be associated with gastrointestinal bleeding (GIB) from different locations or mucosal lesions. We aimed to test this hypothesis.